AB0722 Psoriatic Arthritis Patients without Symptoms of Coronary Artery Disease May Have Higher Presence and Extent of Coronary Plaques Compared To Controls by Coronary CT Angiography. (15th July 2016) - Szentpetery, A.; Brady, D.; Healy, G.; Redmond, C.; Fleming, H.; Duignan, J.; Haroon, M.; Dodd, J.D.; FitzGerald, O.
Abstract : Background: Patients with psoriasis and psoriatic arthritis (PsA) have an increased prevalence of cardiovascular (CV) risk factors, metabolic syndrome (Metsy), and higher risk for subsequent major CV adverse events 1 . Previous studies in rheumatoid arthritis have shown higher coronary plaque vulnerability in patients with coronary artery disease (CAD) compared to controls 2 . Far less is known about CAD in PsA. The extent and composition of coronary plaques have not been studied yet in PsA. Objectives: (1) Study the presence, extent and type of coronary plaques as measured by coronary CT angiography (CCTA) in PsA without symptoms of CAD as compared to controls. (2) To compare plaque measurements between patients with Metsy to those without Metsy (NMetsy) and to controls. (3) Investigate the effect of disease related variables on coronary plaques. Methods: 50 PsA patients (25 Metsy - 25 NMetsy) and 25 controls without CAD (age and sex-matched) underwent 64-slice CCTA. Scans were analysed by 2 readers, blinded to the patients' characteristics. Plaque localisation within the coronary tree, the number of patients with plaque and of affected coronary vessels were assessed. Plaque type was classified into calcified (CP), mixed (MP) and non-calcified plaque (NCP) 3 . Plaque volume was measured for each plaque type and was added to give a total volume (PV) in mm 3 . The number of segments with plaque per patient (segment involvement score (SIS 0–15)) and segment stenosis score (SSS 0–60) were calculated. Kruskal-Wallis test, rank correlations and linear regression analyses were used to study the effect of Metsy and PsA related variables on coronary plaques. Results: Mean age of PsA patients and controls was 58 (±8.3) and 57 (±5.6) years. PsA disease duration was 19 (±7.8) years. 4 (16%) controls had Metsy. 78% of PsA vs 44% of controls had plaques (P=0.007) and the number of affected coronary vessels were higher in PsA (P=0.015). There were more PsA patients with MP and MP volume was higher compared to controls (P=0.006). Mean PV, SIS and SSS were higher in patients with PsA (P=0.002, P=0.032, P=0.004; respectively). Skin and joint related parameters, and CCTA measurements were similar in Metsy vs NMetsy. Plaque presence, PV and SSS were significantly higher in both Metsy and NMetsy compared to controls. SIS (P=0.034) and MP volume (P=0.004) were higher in NMetsy vs controls. Max CRP correlated with PV (r=0.39 P=0.006), SIS (r=0.41 P=0.003) and SSS (r=0.4, P=0.004). Disease duration, max TJC and max CRP had significant effect on the number of affected coronary vessels (P=0.034, P=0.049, P=0.022, respectively). Linear regression analyses revealed no significant relationship between PV and Metsy, whilst diagnosis of PsA (B=0.324 (CI95% 0.05–0.597) P=0.021) and max CRP (B=0.01 (CI95% 0.004–0.019) P=0.006) were independent predictors of PV. Conclusions: This pilot study is the first to assess coronary plaques in PsA using CCTA. PsA patients asymptomatic for CAD had a higher presence and extent of plaques, particularly MP, compared to controls. Our results suggest that PsA may result in accelerated coronary plaque formation independent of metabolic disease. References: Haroon M. JRheumatol 2014 Karpouzas GA. ARD 2015 Pflederer T. Atherosclerosis 2010 Disclosure of Interest: A. Szentpetery: None declared, D. Brady: None declared, G. Healy: None declared, C. Redmond: None declared, H. Fleming: None declared, J. Duignan: None declared, M. Haroon: None declared, J. Dodd: None declared, O. FitzGerald Grant/research support from: Pfizer, AbbVie, BMS, UCB, Consultant for: Pfizer, AbbVie, Janssen, MSD, Cellgene, Novartis, Speakers bureau: Pfizer, AbbVie, Janssen, UCB, Cellgene